Iran's Look East Policy Against Western Countries through Snyder's Foreign Policy Analysis - De Lucas, Juana Clarentine Emmanuela Greevince; Anandito, Muhammad Rayhan; Hendrayudha, Tasya Salsabila; Prakoso, Septyanto Galan (UI Scholars Hub, 2024)
Iran has been in disarray following the United States exit from the JCPOA in 2018. It is due to the increasing number of sanctions reimposed by the West, which harms the Iranian economy. With the current economic downturn, Iran, under President Ebrahim Raisi's leadership, has made efforts to become completely independent from the West by establishing the Look East Policy as its foreign policy. This research analyses why Ebrahim Raisi's administration favoured the Look East Policy as Iranian foreign policy. Data collection techniques used in this study are library research, using secondary data from books, journal articles, official websites, and news articles. Data analysis uses qualitative techniques based on the Foreign Policy Analysis Theory by Richard Snyder. The research findings indicate that the Look East Policy under the Raisi administration reduced Western influence in Iran's domestic economic development and diversified Iran's existing international relations with the Eastern hemisphere with a strengthening intention.